Bone loss in patients with active early rheumatoid arthritis: infliximab and methotrexate compared with methotrexate treatment alone. Explorative analysis from a 12-month randomised, double-blind, placebo-controlled study. Issue 12 (21st April 2009) - Haugeberg, G; Conaghan, P G; Quinn, M; Emery, P
Abstract : Objective: To examine the effect of infliximab plus methotrexate (MTX) compared with placebo plus MTX on bone loss in patients with early rheumatoid arthritis (RA) in a double-blind randomised study design. Further, to explore the associations between bone loss and markers of RA disease. Methods: All 20 patients with RA (10 patients in each treatment group) had active, early RA. Bone mineral density (BMD) was assessed at the hand, lumbar spine (L2–4) and hip by dual energy x -ray absorptiometry at baseline and 12 months' follow-up. Clinical data were collected at regular visits. Results: BMD loss was significantly reduced in the infliximab group compared with the placebo group at the femoral neck (−0.35% vs −3.43%, p = 0.01) and total hip (−0.23% vs −2.62%, p = 0.03) but not at the hand (−2.09% vs −2.82%, p = 0.82) and spine (−0.75% vs −1.77%, p = 0.71). Measures of disease process and joint damage were found to be independently associated with bone loss. Conclusions: This study provides strong evidence of a causal link between inflammation and bone loss in RA. The anti-inflammatory effect of infliximab was potent enough to arrest inflammatory bone loss at the hip but not at the spine and hand.